2004
DOI: 10.1074/jbc.m312320200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of the Lock and Key Motif at the Subunit Interface of Glutathione Transferase P1-1

Abstract: The glutathione transferases (GSTs) represent a superfamily of dimeric proteins. Each subunit has an active site, but there is no evidence for the existence of catalytically active monomers. The lock and key motif is responsible for a highly conserved hydrophobic interaction in the subunit interface of pi, mu, and alpha class glutathione transferases. The key residue, which is either Phe or Tyr (Tyr 50 in human GSTP1-1) in one subunit, is wedged into a hydrophobic pocket of the other subunit. To study how an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 50 publications
5
44
0
3
Order By: Relevance
“…Although it has been suggested that the hydrophobic lock and key interaction is the major interaction between subunit interfaces in all GSTs (7,14,15,25,34,35), the electrostatic attractions definitely enhance the interaction between subunits and play an important role at the dimer interface (22,23,25,36). Electrostatic interactions have also been shown to be involved in both the catalytic reaction and the subunit interactions of the ␦ class GST of Anopheles dirus (37,38) and of the cephalopod class GST (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that the hydrophobic lock and key interaction is the major interaction between subunit interfaces in all GSTs (7,14,15,25,34,35), the electrostatic attractions definitely enhance the interaction between subunits and play an important role at the dimer interface (22,23,25,36). Electrostatic interactions have also been shown to be involved in both the catalytic reaction and the subunit interactions of the ␦ class GST of Anopheles dirus (37,38) and of the cephalopod class GST (39).…”
Section: Discussionmentioning
confidence: 99%
“…Under cellular stress, such as that from oxidative metabolism, however, GSTP1 dissociates from the GSTP1-JNK1 complex, leading subsequently to the activation of JNK (30). This intracellular switch from the monomeric to the dimeric form of GSTP1 and the associated altered JNK signaling provides a mechanism of cellular response to and protection from oxidative and other potentially deleterious stress (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Structural factors that contribute to GSTP1 dimer formation include the hydrophobic lock and key interaction between subunit interfaces and the electrostatic attractions associated with the interactions at the dimer interface (50). Under cellular stress, such as that from oxidative metabolism, however, GSTP1 dissociates from the GSTP1-JNK1 complex, leading subsequently to the activation of JNK (30).…”
Section: Discussionmentioning
confidence: 99%
“…The lock-and-key motif is a common feature of GSTs of the tau, phi, alpha, mu and pi classes [67,75,76]. Only subunits with the same interfacing type appear to be compatible for dimerization.…”
Section: Interactions Between Subunitsmentioning
confidence: 99%
“…The interactions that are involved in assembling the quaternary structure of GSTs include salt bridges, hydrogen bonds, hydrophilic and hydrophobic interactions, including a lock-and-key motif that physically anchors the two subunits together [75][76][77]. The lock-and-key motif is a common feature of GSTs of the tau, phi, alpha, mu and pi classes [67,75,76].…”
Section: Interactions Between Subunitsmentioning
confidence: 99%